Understanding the Ideal End of Life for Older Adults in Cianjur, West Java: From a Religious and Cultural Perspective - DEWI, Puri Swastika Gusti Krisna; PADMAWATI, Retna Siwi; SOENARTO, Yati; SOEBONO, Hardyanto (Journal of Ecohumanism, 2025)
This research explores the aspects of the ideal end of life for older adults in Cianjur, with a specific focus on the religious and cultural aspects that shape perceptions and practices surrounding this significant life stage, using a mixed-methods approach. The study involves 18 qualitative participants—consisting 9 older adults and their respective families—and 160 quantitative participants that spread across Cianjur, West Java, Indonesia. The research specifically focuses on the Indonesian Sundanese Muslim population, exploring how their religious beliefs and cultural traditions influence preferences, practices, and support systems related to aging and the final stages of life, including views on death and the afterlife. By grounding the study within the local context, it provides insights into the interconnected roles of religion and culture in shaping end of life experiences. Through this exploration, the research offers valuable considerations for a religiously and culturally sensitive and holistic approach to caring for aging individuals and addressing end of life care in this unique community setting.